Relationship of blood and semen lead level with semen parameter - Fatima, P; Debnath, BC; Hossain, MM; Rahman, D; Banu, J; Begum, SA; Rahman, MW (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):405-14 The abstract of this article is available on the PubMed website